Konsep Mahabbah Perspektif Abd Al-Karim Al-Qushairi - Fiqri Haikal; Abu Sari (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2020)
In the process of suluk in order to get to God, there are things called maqamat and ahwal. The Sufis of course have different opinions about the number and order of the maqamat itself, and sometimes they have different opinions about something that is obtained by a salik. Is it called maqam or thing? Like the mahabbah, in terms of the definition and distribution of the mahabbah itself, it is also slightly different from one Sufi figure to another. Mahabbah in the Sufi world was first introduced by a female Sufi, namely Rabi'ah al-'Adawiyah. However, in this article, the author will explore the concept of mahabbah according to al-Qushairi. One of the reasons this research is interested in al-Qushairi is that there is still no research related to al-Qushairi's thoughts on the concept of mahabbah. This research is library research. Where the literature data found were reviewed using descriptive analysis. The results of this study are that mahabbah according to al- Qushairi is the nature of God's will related to His desire to specialize a servant with closeness and a high degree. Al-Qushairi divides mahabbah into two, namely the mahabbah of Allah to His servants and the mahabbah of the servant to Allah. As one of the conditions for a salik to be able to occupy the maqam mahabbah, he is not allowed to place or pour out his mahabbah to fellow mahluqs. Because it will result in the failure of a salik to get clarity, peace, and enjoyment of his mahabbah to Allah.